Distribuição espacial dos nutrientes foliares, produtividade e Hypothenemus hampei em Coffea canephora - Silva, Bruno Sérgio Oliveira e (2014)
The detailed knowledge of the spatial variability components involved in plant nutrition can enable the optimization of fertilizer applications improved thus the crop control yield system reducing the costs generated by high input application. The coffee berry borer is the most important pest of the coffee world. Although the bery borer attacks all coffee species but Coffea canephora, conilon variety has characteristics more favorable to their development. The objective of this work was study the spatial behavior of leaves nutrient content, yield and the Hypothenemus hampei behavior in conilon coffee. An irregular mesh with 100 points was installed at each sample point considered by a plant in a crop of high productivity located in São Mateus, Espírito Santo during the 2012 and 2013 harvest. The results were subjected to initial analysis by descriptive statistics and the data were also submitted to geostatistics analysis to define the spatial variability of leaves nutrients levels and yield. The geostatistics technique proved to be an important tool in the study of spatial variability of foliar nutrients, yield and berry borer behavior.